Assessing the use and impact of anti-social behaviour orders - Matthews, Roger 1948-2020 (Researching criminal justice series, 2007)
This book provides one of the first assessments of the widely used but extremely controversial Anti-Social Behaviour Orders (ASBOs) as a method for dealing with anti-social behaviour in the UK.